The relationship between mental health literacy and professional psychological help-seeking behavior among Chinese college students: mediating roles of perceived social support and psychological help-seeking stigma - Yang, Xiao; Hu, Jun; Zhang, Bingren; Ding, Hua; Hu, Danying; Li, Hangdong (Frontiers in Psychology, 2024)
Introduction Mental health literacy is viewed as a significant factor that may facilitate an individual’s pursuit of professional psychological assistance. However, it is important to explore further influencing factors that might underlie this association. This study, employing the framework of the Theory of Planned Behavior (TPB), aims to examine the relationship between mental health literacy and the behavior of seeking professional psychological help, with a focus on the potential mediating roles of perceived stigma and social support in this context. Methods We surveyed 911 college students in seven regions of China (406 males and 505 females, aged between 19 and 25 years old; Mage = 19.65, SD = 1.41) utilizing self-report measures, including the Mental Health Literacy Questionnaire, Professional Psychological Help-Seeking Behavior Scale, Professional Psychological Help-Seeking Stigma Scale, and Perceived Social Support Scale. A chain mediation model was developed to analyze the interconnections between mental health literacy, stigma related to seeking psychological help, perceived social support, and professional psychological help-seeking behaviors. Results The mediation effect analysis indicates that: (1) mental health literacy significantly positively correlates with professional psychological help-seeking behaviors; (2) both perceived social support and professional psychological help-seeking stigma significantly mediate the relationship between mental health literacy and professional psychological help-seeking behavior; (3) perceived social support and the stigma associated with seeking professional psychological help play a chained mediating effect between mental health literacy and the behavior of seeking professional psychological help. Discussion This study found that mental health literacy indirectly facilitates professional psychological help-seeking behaviors by enhancing the perception of social support and reducing the stigma associated with seeking such help. These findings help in understanding how improving mental health literacy and perceived social support while reducing stigma can increase the likelihood of individuals seeking professional psychological assistance. The results are significant for enhancing the utilization of mental health services and implementing mental health education programs in universities.